Reduksi Hak Partisipasi publik Pada Aturan Analisis Mengenai Dampak Lingkungan untuk Perizinan Berusaha di Indonesia: Perspektif Green Constitution - Aditya Prastian Supriyadi (Jurnal HAM, 2023)
The green constitution concept in the Indonesian Constitution is the legal fundamental basis for environmental protection in implementing the national economy through public participation. The rationale for "public participation" as part of the rights of the International Covenant on Civil and Political Rights needs to be examined in Government Regulation instead of Law No. 2 of 2023 concerning Job Creation, passed into a legal act. This writing aims to analyze the components of public participation rights that the job creation act can potentially reduce, especially the provisions on the Environmental Impact Assessment (EIA) in enforcing the green constitution. This research is conducted based on normative legal research methods with statutory and conceptual approaches. The results of this research show that the rules for involving the community in preparing the EIA in the Job Creation Act differ from the green constitution principles in 2 (two) aspects. First, the limitation on community involvement in the Job Creation Act is potentially unconstitutional with the essence of the green constitution and the 1945 Constitution, which guarantees the right of public participation in the environmental field. Second, in the green constitution, the urgency of aspirations for public participation can become a consideration for making more transparent decisions in implementing an economy based on sustainable development. Restrictions on community involvement reduce the concept of a green constitution and potentially reduce the transparency in the granting of business permits in Indonesia which cannot mitigate the risk of environmental losses due to economic exploitation.